Georg Simmel und Gustav Schmoller. Soziologie in Berlin um 1890. Für Otthein Rammstedt (1938-2020) in Dankbarkeit - Dahme, Heinz-Jürgen (Simmel Studies, 2020)
The development of academic sociology in Germany can be dated to the late 1880s. During this time, some scientists offered sociological lectures at German universities for the first time. These, mostly younger scientists came from a wide variety of disciplines; e.g. economics, political sciences, ethnology, psychology of the people (Völkerspsychologie), or philosophy, but didn’t had much in common, except using the word sociology labeling their efforts. Publications for a wider public useing the term sociology had also been available in the past, but were rather attempts at understanding or affirmative legitimizations for the new social policy in the German Empire. Georg Simmel was the first scientist of this ‘sociological generation around 1890’ founding successfully sociology as a new academic subject. The study explores the influence of the then well-known and established economist and political scientist Gustav Schmoller, who also acted at the Berlin University, on the young Simmel.